2017
DOI: 10.1016/j.ijhcs.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the Game Changer Password System: A new approach to password security

Abstract: We proposeand experimentally testa mnemonic variant of password security that uses game positions as passwords. In Experiment 1, we report accuracy and reaction time data when high school student, younger adult, and older adult participants remembered and entered one gamebased password, using chess or Monopoly. In Experiment 2, we report accuracy and reaction time data from participants' use of five game-based passwords across 24 sessions over 10 weeks. All five passwords were stored in chess or Monopoly for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
19

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 41 publications
1
9
0
19
Order By: Relevance
“…If the educational interventions could change their perception, one could argue that this might also reflect on their actual behaviour (Arachchilage et al, 2016). Serious games were also used to help users remember passwords (Tao and Adams, 2008;Malempati and Mogalla, 2011;McLennan et al, 2017). Most recently, McLennan et al (2017) found that a serious game for security education could be fun and usable for different age groups.…”
Section: Serious Games For Security Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…If the educational interventions could change their perception, one could argue that this might also reflect on their actual behaviour (Arachchilage et al, 2016). Serious games were also used to help users remember passwords (Tao and Adams, 2008;Malempati and Mogalla, 2011;McLennan et al, 2017). Most recently, McLennan et al (2017) found that a serious game for security education could be fun and usable for different age groups.…”
Section: Serious Games For Security Educationmentioning
confidence: 99%
“…Serious games were also used to help users remember passwords (Tao and Adams, 2008;Malempati and Mogalla, 2011;McLennan et al, 2017). Most recently, McLennan et al (2017) found that a serious game for security education could be fun and usable for different age groups. Most of this research has been well received when evaluated with users.…”
Section: Serious Games For Security Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…This research showed that sentences make both secure and memorable passwords, thus suggesting that the generally accepted trade‐off between security and memorability is not always true (for a similar idea, see McLennan, Manning, & Tuft, ). This makes long sentences a particularly interesting type of password because they combine both high security and high memorability, thus satisfying the two main characteristics of a good password.…”
Section: Discussionmentioning
confidence: 88%
“…Graphical passwords have been used as a potential solution for the vulnerabilities of alphanumerical passwords because of human memory limitations and/or social engineering complexities. Research has indicated that it is more difficult to decode graphical passwords than textual passwords, for which one can use methods such as brute force attack, dictionary attack, guessing, social engineering and spyware (Bendale et al , 2015; Bhusari, 2013; Chong and Marsden, 2009; Mclennan et al , 2017; Rao et al , 2013; Ray, 2012; Sahu and Singh, 2015). Graphical passwords also help to resolve the weakness of alphanumeric password memorability.…”
Section: Introductionmentioning
confidence: 99%